The Correlation between Low Birth Weight and the Degree of Neonatal’s Kidney Function Impairment in RSUDZA - Cut Zahara Phoenna; Dora Darussalam; Syafruddin Haris; Sulaiman Yusuf; Heru Noviat Herdata; Bakhtiar Bakhtiar (Budapest International Research and Critics University, 2021)
Low birth weight (LBW) is often found in premature birth or because of early gestational age. Several studies have evaluated the impact of Acute Kidney Injury (AKI) on neonates. Birth weight is an important predictor of the nephron and glomerular mass. Mortality in infants with AKI is significantly higher than in those without AKI. Objectives: To analyze the correlation between birth weight and the degree of kidney function disorders. Methods: This study uses an observational analytic approach with a cross-sectional research design. Eighty-nine patients from patients treated from January 2019 to December 2020 were obtained using total sampling. Patient demographic data were collected, and Spearman's test was performed to see the relationship between LBW and the level of impaired renal function in neonates. Results: During the study, 89 samples were obtained, where the mean body length of the neonates was 44.46 ± 2.22 cm, the ureum range was 6-189 mg/dL, the creatinine range was 0.20 -4.03 mg/dL, mean GFR was known to be 19.01+8.96 ml/min/1.73 m2. The highest number of neonates was in the 34–36-week gestational age group. The average birth weight was 1,964.94 ± 274 g, with a range of 1,500-2,400 g. Most neonates had kidney function of risk (31.5%) and injury (30.3%). Only 15 (16.9%) neonates were not affected. Conclusion: There is a significant relationship between birth weight and the level of impaired kidney function (p < 0.05). The correlation coefficient of 0.217 indicates a weak correlation. There was no relationship (p= 0.061) and no significant correlation between gestational age, low GFR (r= 0.189).